Focal Palatitis (Previously Focal Palatine Erosions) in Captive Cheetahs (Acinonyx jubatus) - Steenkamp, Gerhard; Boy, Sonja C.; van Staden, Paul J.; Bester, Marthán N. (Frontiers in Veterinary Science, 2021)
Focal palatine erosion (FPE) is a misleading term that is used in the literature to describe inflammatory lesions associated with depressions of the palatal mucosa in cheetah. Cheetahs have large cheek teeth and these depressions are formed to accommodate them. Previously FPE was only described as a mandibular molar malocclusion on the hard palate due to suspected rotation and super eruption of the mandibular molar of cheetahs aged 18 months and older. Two hundred and fifty six cheetahs (135 male, 121 female), originating from two independent facilities, had their oral cavities evaluated as part of an annual health visit over a decade. Ninety-nine cheetahs were seen once, 59 cheetahs were seen twice, 33 were seen three times, 43 on four occasions, 16 on five occasions, 5 on six occasions, and 1 cheetah was seen seven times. Apart from these clinical cases a prospective study on 5 cheetah cubs (3 male and 2 female) was conducted to document their skull development and mandibular molar eruption over a period of 25 months. Of the 261 cheetahs observed none developed rotation or super eruption of their mandibular molar teeth. The term FPE is a misnomer as these inflammatory lesions were found in palatal depressions opposing any of the cusps of all of the cheetah mandibular cheek teeth. It consisted mainly of deep ulcerations, inflammation and oedema and also micro abscess formation. In severe cases oro-nasal fistulas were present. Of all the depressions present on the cheetah’s palate, the large one palatal to the 4th maxillary premolar was most commonly affected. In the five cubs evaluated prospectively, focal palatitis was evident from the 7 month evaluation, before all the permanent teeth erupted. Conservative treatment of the inflamed depressions by removing the foreign material through curettage and copious flushing reduced the grade of the inflammation when observed on follow-up. Focal palatine erosion is an incorrect term used to describe focal palatitis that occurs randomly in cheetahs. This focal palatitis is often associated with foreign material trapped in the. palatal depressions. Conservative management is sufficient to treat these animals without odontoplasties.